What is the Problem of De Se Attitudes?. - Ninan, Dilip. (Tufts University. Tisch Library., 2017)
Chapter 4 of About Oneself: De Se Thought and Communication, edited by Manuel Garcia-Carpintero and Stephan Torre. .